2014
DOI: 10.15288/jsad.2014.75.290
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control and Implicit Drinking Identity as Predictors of Alcohol Consumption, Problems, and Cravings

Abstract: ABSTRACT. Objective:We investigated trait and alcohol-specifi c self-control as unique predictors and moderators of the relation between implicit drinking identity associations and drinking. Method: Three hundred undergraduates completed a drinking identity Implicit Association Test (IAT), trait and alcohol self-control questionnaires, and alcohol consumption, problems, and cravings inventories. Results: Regression analyses tested for unique effects of predictors and for Self-Control × IAT interactions. Each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…12 Lindgren et al (2014) had observed that the behavior of individuals who becoming alcohol abusers would have a negative effect, not only on the individuals themselves, but also to the people around them. 39 Therefore, Islam as a religion rahmatan lil alamin in psikosufistik teachings had explicitly described that individuals with good self-control would appear as a sense of security for the people around him. 35 Individuals who could provide security for others, named as a believer (in Arabic: Aamin).…”
mentioning
confidence: 99%
“…12 Lindgren et al (2014) had observed that the behavior of individuals who becoming alcohol abusers would have a negative effect, not only on the individuals themselves, but also to the people around them. 39 Therefore, Islam as a religion rahmatan lil alamin in psikosufistik teachings had explicitly described that individuals with good self-control would appear as a sense of security for the people around him. 35 Individuals who could provide security for others, named as a believer (in Arabic: Aamin).…”
mentioning
confidence: 99%
“…Two-process models of addiction therefore predict that the impulsive system will exert primary control over behavior under conditions of reduced motivation and/or opportunity to engage in reflective processing (see also Fazio and Towles-Schwen 1999). Crucially, the capacity to engage in reflective processing is assumed to vary as a function stable differences between individuals (e.g., Farris et al 2010;Lindgren et al 2014;Thush et al 2008;Spruyt et al 2013; but see Pieters et al 2012) as well as temporary factors such as cognitive load, fatigue, and stress (Wiers et al 2010). Accordingly, two-process models of addiction can readily explain the observations that (a) it is difficult to abstain from substance abuse and (b) relapse rates in abstaining patients are typically very high.…”
mentioning
confidence: 99%
“…Findings suggested that implicit alcohol cognition predicted drinking only when self-regulation-most commonly represented by working memory or executive control capacity Salemink & Wiers, 2014;Thush et al, 2008;van Hemel-Ruiter et al, 2015) and self-control (i.e., ability to override a behavioral tendency) (Friese & Hofmann, 2009;Ostafin et al, 2008)-was low (vs. high). However, other studies did not support these interactive effects predicting alcohol use (Lindgren et al, 2014;Pieters et al, 2012). In sum, there is mixed support for whether self-regulation moderates the association between implicit alcohol cognition and alcohol use.…”
Section: Ual-process Models Posit That Alcohol Use Ismentioning
confidence: 88%
“…Initial empirical work examining these two processes in the prediction of alcohol use focused primarily on comparing or pitting each against the other (e.g., O'Connor et al, 2007;Pieters et al, 2010;Thush & Wiers, 2007). However, many dual-process models propose interactive effects of impulsive and self-regulatory processes on alcohol use, and recent work has supported interactive effects (Lindgren et al, 2014;Pieters et al, 2012;Wiers et al, 2010). Most of this work has been done with late adolescent and young adult samples, although there are exceptions (Pieters et al, 2012).…”
Section: Ual-process Models Posit That Alcohol Use Ismentioning
confidence: 99%